Designing UV/VIS/NIR-sensitive shape memory filament yarns. Issue 12 (July 2015) - Tonndorf, Robert; Kirsten, Martin; Hund, Rolf-Dieter; Cherif, Chokri
A novel laser light-sensitive yarn based on a thermoplastic polyester–urethane (TPU) has been prepared and analyzed. Since the thermosensitive shape memory polymer yarn (SMP yarn) has been functionalized using nanoscale heat sources exhibiting light-induced heat generation, the yarn is capable of an optically triggered shape memory effect (SME). For this purpose gold nanorods (GNR) have been employed. In addition to the incorporation of GNR into the yarn, a coating of GNR on the yarn is also proposed, applied by a semi-continuous layer-by-layer (LBL) technique. The SME of the functionalized yarns can be triggered either thermally or optically and has a strain recovery of almost 100%. The light-induced SME is triggered by a low-powered laser (808 nm, 2 W for a GNR-incorporated and 1 W for a GNR-coated TPU yarn). A reference yarn without GNR showed no significant effect. An adaptive structure featuring a SMP-yarn backed shape memory effect has been proposed and demonstrated.